The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1051/0004-6361/202140813
|View full text |Cite
|
Sign up to set email alerts
|

Non-local thermodynamic equilibrium effects determine the upper atmospheric temperature structure of the ultra-hot Jupiter KELT-9b

Abstract: Context. Several observational and theoretical results indicate that the atmospheric temperature of the ultra-hot Jupiter KELT-9b in the main line formation region is a few thousand degrees higher than predicted by self-consistent models. Aims. Our aim was to test whether non-local thermodynamic equilibrium (NLTE) effects are responsible for the presumably higher temperature. Methods. We employed the Cloudy NLTE radiative transfer code to self-consistently compute the upper atmospheric temperature-pressure (TP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 88 publications
2
40
0
Order By: Relevance
“…The large error of the retrieved value indicates that there is a certain degree of degeneracy between [Fe/H] and the T -P profile. In addition, Fossati et al (2021) found that nonlocal thermodynamic equilibrium (NLTE) can affect the upper atmosphere of UHJs. NLTE effects at low pressures can alter the Fe level population and thereby affect the retrieval of the Fe abundance and T -P profile.…”
Section: Retrieval With Carmenes Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The large error of the retrieved value indicates that there is a certain degree of degeneracy between [Fe/H] and the T -P profile. In addition, Fossati et al (2021) found that nonlocal thermodynamic equilibrium (NLTE) can affect the upper atmosphere of UHJs. NLTE effects at low pressures can alter the Fe level population and thereby affect the retrieval of the Fe abundance and T -P profile.…”
Section: Retrieval With Carmenes Datamentioning
confidence: 99%
“…Simulations also indicate that the dayside hemispheres of these planets have temperature inversion layers because the absorption of the stellar radiation by species such as metals and metal oxides is strong (e.g., Lothringer & Barman 2019;Baxter et al 2020). It has recently been shown that for the hottest exoplanet KELT-9b, the deviation from local thermodynamic equilibrium in the level population of Fe II is the main driver of strong temperature inversion in the high-altitude atmosphere (Fossati et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It is thus probably not a casualty that all the detections of temperature inversion with high-resolution spectroscopy up to now are for UHJs orbiting A-type stars. These stars have strong UV emission, which is the wavelength range where the metals causing temperature inversions present the largest number of lines (Fossati et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, one key characteristic is the atmospheric thermal inversion, which appears to happen when the equilibrium temperature reaches ∼1700 K, with observational evidence for a transition between the two regimes (Baxter et al 2020). Fossati et al (2021) showed that non-LTE effects play a significant role in determining the shape of the temperature inversion. While previous studies predicted the temperature inversion to be caused mainly by TiO and VO (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For pressures greater than ∼ 10 −6 bar (which encapsulates all of the pressures probed in our GCM) LTE and NLTE models were nearly identical in predicting hydrogen level populations. In Fossati et al (2021), they use NLTE as a framework for pressures less than 10 −4 bars when modeling temperaturepressure profiles. For pressures greater than 10 −4 bars, they note that the retrieved temperature profiles are very similar.…”
Section: Discussionmentioning
confidence: 99%